Biomass and coal co-feed power and SNG polygeneration with chemical looping combustion to reduce carbon footprint for sustainable energy development: Process simulation and thermodynamic assessment. (September 2018) - Fan, Junming; Hong, Hui; Jin, Hongguang
Abstract: In this paper, biomass and coal has been used as blending feedstock for synthetic natural gas (SNG) production to originally shift H2 /CO ratio in syngas during gasification step that benefits downstream methanation process. The recycling ratio of unreacted gas is controlled to avoid huge exergy destruction during methanation, thus providing opportunity for supplementary power generation. The remaining gas is directed to chemical looping combustion (CLC) for power generation, and carbon capture is inherently achieved. Besides capture and storage of photosynthetically-derived CO2 from biomass by means of CLC offers possibilities for negative greenhouse gas emissions. The energy efficiency and exergy efficiency of this proposed process are 53.19% and 50.81%, respectively. Meanwhile approximately 16.86% of energy consumption and 98.74% of carbon emissions have been reduced compared with standalone reference system. In terms with the captured CO2 quality, it meets the requirement of suggested restrictions at biomass share of 40% (wt. %). Within this biomass share, the oxygen-to-carbon ratio ( O/C ), steam-to-carbon ratio ( S/C ), and recycling ratio of unreacted gas ( Ru ) have been found to be optimum at 0.4, 0.5 and 0.7, respectively. Highlights: Biomass and coal co-feed feedstock benefits synthetic natural gas production. Integration of chemical looping combustion for polygeneration pays no energy penalty for carbon capture. The energy efficiency of this proposed process is 53.19% with zero-carbon emissions.